Cultivating cross-cultural collaborations: perspectives from the Developing Belief Network - Richert, Rebekah A.; Corriveau, Kathleen H. (Frontiers in Developmental Psychology, 2025)
Developmental science has long highlighted the limitations in generalizability arising from the fact that the sizable majority of the populations we study come from a minority of locations globally. Furthermore, team science has lauded the opportunities presented by collaborative approaches to science, while open science approaches highlight the need to ensure that methods and data adhere to principles that are FAIR (findable, accessible, interoperable, and reusable). Challenges to employing both a global sampling strategy and a team/open science approach, while centering cultural influences and diversity in early development, include challenges designing protocols that provide both standardization and cultural sensitivity, working with and interpreting data from unique samples, structural challenges focused on meeting the requirements needed for tenure and promotion, and ethical challenges with making data from minors fully accessible. Here, we present lessons we have learned from cultivating the Developing Belief Network, outlining our solutions toward mitigating these challenges. We highlight our approach to constructing and sustaining the DBN, as well as recommendations we have learned from the 5 years since its inception.